Determinants of serve action in high level male volleyball - Araujo, R.; Moraes, C.; Coutinho, P.; Mesquita, I. (World Congress of Performance Analysis of Sport IX, 2012)
Throughout the evolution of Volleyball as a game, serve has been one of the most important game actions that contribute for game result (Marcelino et al., 2008; Yiannis & Panagiotis, 2005). In this way, the purpose of the present study was to examine probabilistic relationship within the dynamics of serve action in high-level men`s volleyball. The sample of this study comprises 1698 serve actions, corresponding to 19 games of the 10 best teams that participated in the 2006 FIVB Men`s World Championships. Two independent variables were considered: (i) server player: setter, opposite, left-side attackers and middle-attackers; and (ii) type of serve (Lirola, 2006): jump serve, jump floating serve and jump tennis serve. Serve effect was also considered as dependent variable: error, easy serve (allow all attack options), moderate serve (without all attack options), hard serve (do not allow attack organization) and serve point. A multinomial logistic regression was applied with a significant level established in 5%. Results showed that both server player and type of serve were predictive determinants of serve effect Chi2(20) = 121.500, p<0.001). Middle-attackers are the less effective servers, creating more facilities to opponent`s attack organization. Despite the setters and left-side attackers presented more errors and less effective serves, those players also presented more serves resulting in point than opposite player. Although opposite player didn`t showed more points and errors, it was this server that caused more difficulties to opponent`s attack. According to the type of serve jump serve not only caused more points but also more errors. Jump tennis serve didn`t show influence in the serve effect. As conclusion, the present study suggests server player and type of serve as determinants for the serve effect and therefore to the opponent`s attack organization. From these results some implications can be withdrawn for practice and competition, namely a better used of power jump serve and more opportunities to other players practice their serves.